Experience of personnel involved in dead body management at an apex institute in the aftermath of Odisha triple train collision. - Praisy Joy; Prajna Paramita Giri; Madhumita Patnaik; Prabhas Ranjan Tripathy; Manisha Rajanand Gaikwad; Pravash Ranjan Mishra; Sanjukta Sahoo; Sipra Rout; Kumbha Gopi; Dilip Kumar Parida; Ashutosh Biswas (PLoS ONE)
Background Railway disasters cause huge loss of life and resources. A triple train collision occurred at 7 PM on 2nd June 2023 at Bahanaga, Balasore, Odisha. It was the third deadliest train accident in India with 288 deaths and more than 900 injured. This study aimed to bring out the experience and capture the emotions of the personnel involved in body management of this major accident. Materials and methods This qualitative questionnaire-based study was done between 13/07/2023 and 29/01/2024, involving 47 personnel (including faculty, residents, staff, and students) who managed the deceased bodies. Six open-ended questions dealing with the experiences of the body management team were analyzed using thematic analysis framework method. Quirkos software was used to generate themes and subthemes. Another six questions about self-reported satisfaction levels of the personnel were graded on a Likert scale of 1 to 5. Results Qualitative analysis identified six themes and twelve subthemes. It highlighted critical aspects such as lack of training in managing mass tragedies, inadequate flow of essential supplies, emergency preparedness, and defined standard operating procedures (SOP). Excellent teamwork (91.4% of participants expressed high satisfaction with the teamwork) and on-the-spot decision-making were heralded as strengths. The Likert scale showed that 87.2% of participants rated the overall dead body management at 4 or 5. Furthermore, 93.6% (44/47) of participants gave a score 4 or 5 for Tagging and Embalming. Conclusions Teamwork and proper embalming were identified as the top-rated contributors towards effective body management. Recommendations suggested were mock drills and refresher courses in body management for all stakeholders and psychological support to handle the emotional toll of managing mass tragedy. The identification and embalming of dead bodies are an essential humanitarian service and it helped bereaved families to say a final farewell to their loved ones.